21-Year-Old Pregnant Woman with MODY-5 Diabetes. (15th October 2017) - Mikuscheva, Anastasia; McKenzie, Elliot; Mekhail, Adel
Abstract : The term "Maturity-Onset Diabetes of the Young" (MODY) was first described in 1976 and is currently referred to as monogenic diabetes. There are 14 known entities accounting for 1-2% of diabetes and they are frequently misdiagnosed as either type 1 or type 2 diabetes. MODY-5 is an entity of monogenic diabetes that is associated with genitourinary malformations and should be considered by obstetricians in pregnant women with a screen positive for diabetes, genitourinary malformations, and fetal renal anomalies. Correct diagnosis of monogenic diabetes has implications on managing patients and their families. We are reporting a case of a 21-year-old pregnant woman with a bicornuate uterus, fetal renal anomalies, and a family history of diabetes that were suggestive of a MODY-5 diabetes.